Sovereignty in the Italian polling booths. Issue 5 (20th October 2019) - Pasquino, Gianfranco; Valbruzzi, Marco
ABSTRACT: This article provides a general interpretation of the 2019 European parliamentary elections, with a special focus on the vote in Italy and on its consequences for the functioning of the Italian political system. It also offers a short description of the articles included in this special issue dedicated to the 2019 E.U. election. In the last section this introduction discusses critically the interpretation of the 2019 European vote as a case of so-called 'second-order elections'.